Comparison between Two Different Techniques of Botulinum Toxin-A Injection for Treatment of Anterior Gummy Smile After Orthodontic Treatment - Abanoub Adeeb Fekry Hanna; Mohamed Elsayed Saad Ibrahim; Wael Mohamed Mobarak Refai (International Journal of Medical Toxicology and Legal Medicine, 2024)
Thirty-four anterior gummy smile patients underwent orthodontic treatment then divided randomly into two equal groups for botulinum toxin-A (BTX-A) injection. Group A received 1 BTX-A injection per side (Yonsei point). Group B received 3 injections of BTX-A per side. All patients were assessed at 2, 4, 12 and 24 weeks post-injection. They were satisfied by the results,especially after 1 month. Group B showed more improvement at canines regions than group A. It was concluded that BTX-A injection is a safe, satisfying method for anterior gummy smile patients. Multiple injections are more preferred than one injection.